Comparison of BCH Code Performance in LTE-Advanced Cooperative System in Suburban, Urban and Rural Environment Based on WINNER II Channel Model - Fadhil, Mohammed; Abu-Samah, Asma; Nordin, Dr Rosdiadee; Ismail, Mahamod; Abdullah, Nor Fadzilah (International Journal of Integrated Engineering, 2021)
Multi-path fading is a severe issue that causes fluctuations in the amplitudes of the received signals. For combating this issue, several researchers have used cooperative communication in a Long-Term Evolution (LTE)-advanced system. Furthermore, for decreasing the degradative effects of transmitted signals, various error correction techniques can be used for recovering the erroneous components, especially when the channel has been deep fading. Here, the researchers have investigated the general performance of the Convolutional Codes (CC) in the LTE-advanced cooperative system. They also checked the performance of this LTE-advanced cooperative system, which uses Bose–Chaudhuri–Hocquenghem (BCH) codes and implanted the WINNER II project as the channel model between the nodes in the two coding processes, i.e., CC and BCH. They studied three different environments (i.e., a suburban macro-cell, urban macro-cell, and the rural micro-cell) for understanding the appropriate relay height in every environment. Simulation studies were also conducted, which showed that the use of the CC and the BCH codes in the relay technologies could significantly increase the system performance with regards to the comparison between the BER and the direct connection. It was noted that the performance of the system which used BCH nodes was better than the system using CC nodes in an LTE-advanced cooperative system.